Hungarian Monitoring, 16 March 1990 . [Magyar rádiófigyelő], 1990. március 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: CPSU Central Committee plenum, West German press speculates on Gorbachev's political chances - War of words between Moscow and Vilnius - GDR election campaign makes strides Domestic Affairs: - March 15 celebrations in Washington - George Bush receives László Tőkés - Election campaign: constitutional lawyer on arrangements for ballot secrecy, conflict between Alliance of Free Democrats (SZDSZ) and committee overseeing TV and radio, Independent Smallholders' line on land questions softens, parliamentary candidate Verbóczky assaulted - Situation of Hungarians in Transcarpathia Külpolitika: - SZU: az SZKP-KB plénum, Gorbacsov politikai esélyeit latolgatja a nyugatnémet sajtó - Üzenetháború Moszkva és Vilnius között - Hajránál tart a választási kampány az NDK-ban Belpolitika: - Washingtoni márc. 15-i ünnepség - George Bush fogadta Tőkés Lászlót - Választási kampány: az alkotmányjogász a szavazás titkosságának feltételeiről, háború a SZDSZ és a TV és Rádió felügyelő bizottsága között, a földkérdésben enyhült a Kisgazda Párt álláspontja, Verbóczky képviselőjelölt bántalmazási ügye - A kárpátaljai magyarság helyzete